O discurso do grotesco na mídia digital - Carvalho, Adriano Cesar Lima de (2013)
This study presents our research on the discourse of the grotesque in digital media, specifically in two blogs. We rely on the theoretical-conceptual and methodological discourse analysis of the French School. We analyzed a set of posts in the following blogs: Eu Sou Ryca and Cleycianne, and we did it based on some propositions on the discourse of the grotesque by Mikhail Bakhtin (1999a), Muniz Sodré and Raquel Paiva (2002), Wolfgang Kayser (2003) and Mary Russo (2000). The expressions of the grotesque analyzed in the blogs Eu Sou Ryca and Cleycianne result predominantly in humorous effect, obtained by means of irony and parodization, which calls for ridicule and relegation, through a strong tension between the beautiful and the ugly, the socially acceptable and the aberration, the taste for the strange and the aesthetically striking. The grotesque appears initially as a significant feature of ornamental paintings found in Roman caves in the late fifteenth century, and today it can be seen permeating from sculptures, paintings, literary works, talk shows for television, videos hosted in cyberspace, specifically in the collective domain of weblogs. This work seeks to analyze how the discourse of the grotesque constitutes the humorous process in its insertion in cyberspace